THE EFFECTS OF RENAL HYPERTENSION ON THE VESSELS OF THE EARS OF RABBITS - Abell, R. G. (The Rockefeller University Press, 1942)
1. The present experiments demonstrate by direct observation that peripheral arterioles in moat chambers in rabbits' ears constrict during the development of renal hypertension, and that they remain persistently constricted, although not sufficiently to interrupt the blood supply to the tissues. The arteriolar constriction in the hypertensive animals was not dependent upon nerves, since it occurred in newly formed arterioles which had probably never been supplied with nerves, as well as in older arterioles with a functional nerve supply. 2. No capillary constriction was observed during or following the development of hypertension, although the walls of the capillaries could be very clearly seen. Persistent hypertension was associated in two examples with increased sticking of leukocytes to the walls of the capillaries and venules, some emigration of leukocytes, and a few small hemorrhages. 3. During development of hypertension, new arteriovenous anastomoses were observed to appear in the chambers. 4. No evidence of change was noted in the viscosity of the blood or in the appearance of the blood corpuscles in the hypertensive rabbits. 5. The constriction of the arterioles during and following the development of hypertension closely resembled that produced by intravenous injections of angiotonin.